Selected features of small and medium-sized enterprises related to international entrepreneurship: an empirical analysis - Olejniczak, Karolina; Dębicka, Anna (Wybrane cechy małych i średnich przedsiębiorstw powiązane z międzynarodową przedsiębiorczością: badania empiryczne, 2020)
The research presented in the article is part of the current trends in research on international entrepreneurship, in particular in the field of the comparisons and premise for sustainable development and the success factors in the international arena. The main purpose of this work was to examine the characteristics and determinants affecting international activities of small and medium-sized enterprises in Poland. The authors created a research model which checked the importance of selected characteristics of enterprises and their impact on international activity. This allowed to check whether and to what extent individual features of enterprises, business activity, including development strategy, and policies to stregthen the competitiveness and cooperation with business environment instututions are correlated with international activities. The study showed significant differences between enterprises that carry out international activity and those which limit their activity only to the domestic market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 153-167